Room temperature copper-catalyzed oxidative amidation of terminal alkynes for the synthesis of α-ketoamides using O-benzoyl hydroxylamines as aminating reagent and oxidant. Issue 82 (17th August 2016) - Shen, Guodong; zhao, Lingyu; Wang, Yichen; Zhang, Tongxin
Abstract : A novel and convenient copper-catalyzed oxidative amidation for the synthesis of α-ketoamides has been successfully developed, which uses easily available O -benzoyl hydroxylamines as aminating reagent and oxidant. Abstract : A novel and convenient copper-catalyzed oxidative amidation for the synthesis of α-ketoamides has been successfully developed, which uses easily available O -benzoyl hydroxylamines as aminating reagent and oxidant. The reaction proceeds smoothly at room temperature and is compatible with a range of substrates to give the desired products in moderate to good yields.